2015
DOI: 10.1080/09540121.2015.1124974
|View full text |Cite
|
Sign up to set email alerts
|

HIV stigma intervention in a low-HIV prevalence setting: a pilot study in an Egyptian healthcare facility

Abstract: This pilot study is the first to evaluate stigma-reduction intervention in a healthcare setting in Egypt and in the Middle East and North Africa region. It also contributes to knowledge on how to address stigma in low-HIV prevalence settings. A quasi-experimental study design was used to evaluate the effect of anti-HIV stigma intervention in one hospital in Egypt. A control hospital was selected and matched to the intervention hospital by type, size and location. The intervention focused on HIV-related stigma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…This includes a recognition of the importance of addressing stigma in health facilities [72], yet concerted efforts to tackle stigma at any scale within countries are lacking, apart from Thailand [73]. One reason for such inaction may be the small, but growing, body of evidence of effective intervention models for HIV‐stigma reduction, particularly in health facilities [46,49‐56]. This paper adds to that literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes a recognition of the importance of addressing stigma in health facilities [72], yet concerted efforts to tackle stigma at any scale within countries are lacking, apart from Thailand [73]. One reason for such inaction may be the small, but growing, body of evidence of effective intervention models for HIV‐stigma reduction, particularly in health facilities [46,49‐56]. This paper adds to that literature.…”
Section: Discussionmentioning
confidence: 99%
“…Yet despite this evidence and global recognition of the need to tackle stigma – especially in health facilities – there is little concrete evidence of concerted efforts by countries and donors to scale‐up stigma‐reduction interventions in health facilities within national HIV responses. This may be in part due to the still nascent body of evaluated intervention approaches to stigma‐reduction in health facilities [46,49‐56].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review found evidence of the impact of these types of human rights programmes (singly and combined) on HIV‐related outcomes for people living with HIV and key and vulnerable populations most at risk of HIV, ranging from decreased HIV risk behaviours to increased HIV testing to reduced incidence . The review examined research published between 2003 and 2015, but evidence of the positive impact of similar interventions both prior to and after these dates have also been published; for example, focusing on the training of health workers to reduce stigma and programmes promoting legal literacy and advocacy . Advocacy targeting discriminatory laws, policies and practices have also been shown to be effective to removing barriers to HIV services , while evidence of the effectiveness of sensitizing law enforcement is increasing .…”
mentioning
confidence: 99%
“…The low HIV diagnosis rate observed in many countries in the MENA region, including Oman, could be attributed to several factors. A major reason is the high levels of HIV-related stigma and discrimination, which preclude access to HIV services (Feyissa et al, 2019;Lohiniva et al, 2016). Moreover, user-friendly services targeting key populations are limited.…”
Section: Discussionmentioning
confidence: 99%